WAWASAN NUSANTARA & KEBUDAYAAN BAHARI - Primadi Tabrani (Jurnal Dimensi Seni Rupa dan Desain, 2008)
AbstractThis essay brings up the idea of home country, archipelago and Bhineka Tunggal Ika ( unity in diversity ) as a united history. It starts with the existence of archipelago and it leads to the establishment of tribes and the establishment of different areas with its European pluralism. In the other hand, the establishment of tribes comes first and it is followed by the appearance .of a nation which pluralism is involved in it.         •AbstrakTulisan ini mengetengahkan munculnya tanah air, wawasan Nusantara dan Bhinneka Tunggal Ika sebagai satu kesatuan sejarah yang diawali dengan munculnya Wawasan Nusantara kemudian kesatuan, baru suku dan daerah yang berbeda dengan kebangsaan dan pluralismenya Eropa. Di "barat" yang muncul adalah etnik dulu, baru kemudian muncul bangsa dan setelah itu baru pluralisme.